Factors associated with severe disease from malaria, pneumonia and diarrhea among children in rural Tanzania – A hospital-based cross-sectional study - Kahabuka Catherine; Kvåle Gunnar; Hinderaker Sven (BMC Infectious Diseases, 2012)
Abstract Background Mild cases of malaria, pneumonia and diarrhea are readily treatable with complete recovery and with inexpensive and widely available first-line drugs. However, treatment is complicated and expensive, and mortality is higher when children present to the hospital with severe forms of these illnesses. We studied how care seeking behaviours and other factors contributed to severity of malaria, pneumonia and diarrhoea among children less than five years in rural Tanzania. Methods We interviewed consecutive care-takers of children diagnosed with malaria, pneumonia and/or diarrhea at Korogwe and Muheza district hospitals, in north-eastern Tanzania, between July 2009 and January 2010, and compared characteristics of children presenting with severe and those with non-severe disease. Results A total of 293 children with severe and 190 with non-severe disease were studied. We found persistent associations between severity of disease and caretaker’s lack of formal education (OR 6.6; 95% confidence interval (CI) 2.7-15.8) compared to those with post-primary education, middle compared to high socio-economic status (OR 1.9; 95% CI 1.2-3.2), having 4 or more children compared to having one child (OR 2.5; 95% CI 1.4-4.5), having utilized a nearer primary health care (PHC) facility for the same illness compared to having not (OR 5.2; 95% CI 3.0-9.1), and having purchased the first treatment other than paracetamol from local or drug shops compared to when the treatment was obtained from the public hospitals for the first time (OR 3.2; 95% CI 1.9-5.2). The old officially abandoned first line anti-malaria drug Sulfadoxin-pyrimethamine (SP) was found to still be in use for the treatment of malaria and was significantly associated with childrens’ presentation to the hospital with severe malaria (OR 12.5; 95% CI 1.6-108.0). Conclusions Our results indicate that caretakers with no formal education, with lower SES and with many children can be target groups for interventions in order to further reduce child mortality from treatable illnesses. Furthermore, the quality of the available drug shops and PHC facilities need to be closely monitored.